MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MEDIA POPILINK BERKARAKTER PADA MATA PELAJARAN IPS - Ahmad Taufik (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
Along with the development of science and technology, especially information and communication technology, computer as a learning medium becomes unavoidable. Learning IPS with conventional strategies that have been applied to cause the learning takes place passively, less attractive, unidirectional, less able to motivate students, providing an atmosphere of learning less passionate, less can involve student activity which eventually resulted in the achievement of student learning outcomes rendah.Berangkat of phenomena mentioned above, researchers interested in conducting research related to the effective use of media popilink character in social studies to improve motivation and learning outcomes media siswa.Penggunaan popilink character in SMPN 2 Jogoroto able to increase students' motivation with the criteria very well with the results as follows: ( 1) students are very enthusiastic and responsive following the learning process; (2) students are more daring in giving answers through the slides shown (3) the results of student learning was satisfactory. Other findings showed 35 students were given a questionnaire, 34 (97.14%) stated that learning Character Popilink media can facilitate students understand the subject matter by the teacher. While 35 (100%) of students feel that learning with media Popilink Character can train students to behave honest, serious, focused and enthusiastic in participating in the competency test.